2001
DOI: 10.1007/s11910-001-0085-8
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s disease: The treatment of drug-induced hallucinations and psychosis

Abstract: Drug-induced psychosis is one of the most disabling complications of advancing Parkinson's disease. It has also been one of the most difficult to treat. Clozapine was the first medication shown to be safe and effective in this setting, and it remains the standard by which newer atypical antipsychotics are measured. However, due to the small but significant risk of agranulocytosis and the need for frequent blood testing, alternatives have been sought. Risperidone, olanzapine, and quetiapine are new atypical ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Most of the previous studies have reported auditory hallucinations occurring as a part of visual hallucinations[25273031] which was also seen in our study. Pure auditory hallucinations are rare in PD and there has been no systematic report of auditory hallucinations in PD.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Most of the previous studies have reported auditory hallucinations occurring as a part of visual hallucinations[25273031] which was also seen in our study. Pure auditory hallucinations are rare in PD and there has been no systematic report of auditory hallucinations in PD.…”
Section: Discussionsupporting
confidence: 89%
“…Molho et al .,[30] reported visual hallucinations in about 30% of patients. They described the presence of animals and inanimate objects as a part of visual hallucinations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agents such as mescaline that affect catecholaminergic systems, promoting the release of dopamine, are said to result in multi-coloured images of fantasy. The dopaminergic system is frequently implicated in disease-related visual hallucinations, especially in Parkinson's disease, on the basis of symptomatic treatment with neuroleptics such as clozapine (Devanand & Levy 1995;Molho & Factor 2001), which commonly target the D2 receptor subtype (although other pharmacological actions may be implicated), and on the basis of the induction of hallucinations by levodopa (Ldopa) (Cannas et al 2001;Goetz et al 2001a;2001b;Holroyd et al 2001). However, in Parkinson's disease, evidence that L-dopa is the principal contributing factor to hallucinations is not consistent, since increasing L-dopa medication does not increase hallucination prevalence (Goetz et al 1997;1998a).…”
Section: Panoramic Hallucinationsmentioning
confidence: 99%
“…The dopaminergic system is frequently implicated in disease-related visual hallucinations, especially in Parkinson's disease, on the basis of symptomatic treatment with neuroleptics such as clozapine (Devanand & Levy 1995;Molho & Factor 2001), which commonly target the D2 receptor subtype (although other pharmacological actions may be implicated), and on the basis of the induction of hallucinations by levodopa (Ldopa) (Cannas et al 2001;Goetz et al 2001a;Holroyd et al 2001). The dopaminergic system is frequently implicated in disease-related visual hallucinations, especially in Parkinson's disease, on the basis of symptomatic treatment with neuroleptics such as clozapine (Devanand & Levy 1995;Molho & Factor 2001), which commonly target the D2 receptor subtype (although other pharmacological actions may be implicated), and on the basis of the induction of hallucinations by levodopa (Ldopa) (Cannas et al 2001;Goetz et al 2001a;Holroyd et al 2001).…”
Section: Pharmacologically Induced Hallucinationsmentioning
confidence: 99%